1980
DOI: 10.1002/pi.4980120303
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Reinforcement: The Influence of Bound Polymer

Abstract: The reinforcement of rubbers by colloidal filler particles has often been associated with the presence of ‘bound polymer’, that polymer which cannot be removed by solvent extraction from the filled material. This paper demonstrates to the contrary that, for filled polyethylene, bound polymer is observed but reinforcement is not. Indeed, the bound polymer appears to embrittle the filled material. A new model of the filler‐polymer interface is proposed to account for these results. It is suggested that there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…According to Kendall and Sherliker, 31 the role of a filler as a reinforcement is influenced by the surface interaction between the polymer and filler, resulting in a layer of polymer adhering to the filler surface. This polymer interphase causes energy dissipation and toughness in a filled material.…”
Section: Impact Propertiesmentioning
confidence: 99%
“…According to Kendall and Sherliker, 31 the role of a filler as a reinforcement is influenced by the surface interaction between the polymer and filler, resulting in a layer of polymer adhering to the filler surface. This polymer interphase causes energy dissipation and toughness in a filled material.…”
Section: Impact Propertiesmentioning
confidence: 99%
“…For example, poly-(ethylene) composites filled with silica do not exhibit any reinforcement, as measured using tear strength, until the bound polymer chains are long enough to allow for entanglements. 39 Additionally, a mean-field-like tube model has been developed to describe polymer-filler junctions in carbon black filled poly(butadiene) and SBR where modulus increases are concluded to emanate from entanglements between the bound polymer and the free polymer. 40 Thus, we suggest that the modulus enhancements observed herein also arise from interactions between the bound and the free polymer in the matrix.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…24 The gain in both the impact and tensile strengths of PP/CaCO 3 composites demonstrated that REC not only promoted the wettability and dispersity of CaCO 3 in the PP matrix, but it also provided some degree of adhesion between the treated filler and matrix. However, the unremarkable difference in tensile strength between composites with and without REC revealed that the interaction in such systems was weak.…”
Section: Figurementioning
confidence: 98%